The Effect Of Etch Depth To SOI Large Cross-Section Rib Waveguide - Nurdiani, Zamhari; Abang Annuar, Ehsan; Nordiana, Rajaee; Abdul Rahman, Kram; Dyg Nur Salmi Dharmiza, Awg Salleh (Science and Engineering Research Support Society, 2020)
Silicon-on-insulator (SOI) with large cross-section rib waveguide (LCRW) has become one of the popular geometry used to design simple optical devices. Other than the advantages of the SOI material itself, the LCRW can avoid polarization issue and decrease the waveguide-fiber coupling loss. The dimension of the LCRW such as rib width, rib height, slab height and etch depth is identified to ensure it is compatible with its use. This research is to investigate the effect of the etch depth in SOI LCRW design. The objective of this research is to simulate and analyze the SOI LCRW with the changes of etch depth using beam propagation method. The waveguide has been designed in OptiBPM software where the single-mode field is simulated by OptiBPM mode solver. The downstream transmission wavelengths used in this research are 1480 nm data and 1550 nm video signals. Besides, the single-mode condition stated by Soref, Pogossian and effective index method is used. This analysis finds that the higher the value of the etch depth the less the width value of rib to maintain a single-mode propagation in SOI LCRW transmission. Moreover, out of the three single-mode condition stated, the single-mode condition by Soref allow greater LCRW width.